Penataan Manajemen Administrasi Madrasah Diniyyah Tarbiyatul Ulaa Derepan Menoreh Salaman Magelang - Nailatul Muna; Arina Millataka; Ahmad Fatkhul Mujib (Khidmatan, 2021)
This community service program aims to implement the tri dharma of higher education and as a form of student learning about society. The service program carried out in Derepan Hamlet, Menoreh Village, Salaman District, focused on Islamic education management by structuring the administrative control of the Madrasah Diniyyah Tarbiyatul Ulaa institution as one of the educational institutions in Derepan Hamlet. This organizational management arrangement is expected to help Islamic educational institutions Madrasah diniyyah Tarbiyatul Ulaa be orderly and well-organized so that the teaching and learning process in Madrasah diniyyah can run well produce graduates who are competent in religious knowledge.